FAKTOR PENYEBAB BERHENTINYA SANTRI YANG SUDAH BISA MEMBACA AL-QUR’AN DAN SOLUSINYA - Toybul Ardhan; Hasan Basri (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Every Muslim is required to study the Qur'an so that according to what was taught by the Prophet read according to ability, calmly, and repeated so that it is really true. Reading it and practicing it is a very noble deed and will get a double reward. The purpose of this research is to find out the factors causing the cessation of students who can already read the Koran and the solution at Madrasah Diniyah Raudhatul Jannah, Sukorejo Village, Sidayu District, Gresik Regency. While this research uses a qualitative approach, this type of case study. Based on the presentation and discussion of research data, it can be concluded that the factors causing students not to continue learning the Koran: (1) child factors, (2) family, (3) playmates, and (4) IT development. While the solutions are (1) for the ustad to provide an understanding to the parents of the students, how important it is to learn the Qur'an, and (2) for the ustad to remain enthusiastic about learning al-Qur'an learning methods so that the students do not seemed bored and would feel at home still studying at Madrasah Diniyah Raudhatul Jannah. Continuing to read and practice the Qur'an is caused by internal factors and external factors that make students leave the routine of studying the Qur'an.